Analisis Kesalahan Kebahasaan pada Hasil Menulis Teks Prosedur Siswa Kelas VII SMP - Carolin, Margareth (Indonesian Journal of Applied Linguistics Review, 2023)
This study aims to analyze the linguistic errors found in the procedural text writing of seventh grade junior high school students. A procedural text is a type of text that provides instructions on the steps to perform an activity in a clear sequence. The analysis was conducted by identifying the types of linguistic errors occurring in the text structure, sentence usage, grammar, and spelling.  The research method used was descriptive qualitative, with a data analysis technique involving the classification of linguistic errors based on their types. The results of the analysis indicate that the most dominant errors were related to punctuation usage, improper use of imperative verbs, and errors in sentence structure that do not conform to language rules. This study provides recommendations for teaching Indonesian at the junior high school level to place more emphasis on linguistic learning that adheres to the correct procedural text writing conventions.